Characteristics of cybercrimes: evidence from Chinese judgment documents. (2nd November 2018) - Cai, Tianji; Du, Li; Xin, Yanyu; Chang, Lennon Y.C.
ABSTRACT: China has witnessed a rapid growth in internet use alongside an unprecedented increase in cybercrimes. Although studies have suggested that there are many factors that may contribute to the growing number of cybercrimes, such as the widespread use of online gaming, the low average income of internet users, and an increased access to IT skills, systematic analyses of actual convictions are rare. As the level of domestic cybercriminal activities increases rapidly, there is a growing call for empirical studies on cybercrime in China. Through the extraction of data from China Judgements Online, the newly released Chinese judgements service, this study examines the basic characteristics of cybercrimes in China by analysing 448 sentencing documents that cover four types of computer crimes: online frauds, real asset theft, virtual asset theft, and stolen accounts. We analyse cybercrime cases from the perspective of the underground economy, focusing on the roles that cybercriminals play in the value chains of the online underground market; more specifically, what kind of products and services are enabled through cyber theft, and how those products and services are integrated as components of the underground economy.